Kinetics of the free-radical polymerization of isobornyl methacrylate in the presence of polyisobutylenes of different molar masses - Soulé, Ezequiel Rodolfo (2005)
The scope of this study was to investigate the effect of a linear polymer dissolved in a reactive monomer on the kinetics of free-radical polymerization before the start of phase separation. The selected system was a solution of polyisobutylene (PIB) in isobornyl methacrylate (IBoMA), polymerized at 80 °C in the presence of benzoyl peroxide (BPO). A ternary phase diagram of PIB, IBoMA, and poly(isobornyl methacrylate) (PIBoMA) was built at 80 °C, both employing physical blends or determining the phase separation conversion in the course of polymerization. Cloud-point curves (CPC) obtained by both methods were coincident within experimental error. They were shifted to lower conversions when increasing the molar mass of PIB. Different PIBs exhibiting CPC at advanced conversions were selected for the kinetic study performed employing differential scanning calorimetry (DSC) at 80 °C. A simple kinetic model for free-radical polymerizations describing the relevant termination rate constant in terms of the free-volume theory provided a consistent fitting of the polymerization rates in the conversion range where the solution remained homogeneous. Increasing the molar mass of PIB led to an increase in polymerization rate due to the decrease in free volume and the corresponding decrease of the termination rate. Increasing the amount of a particular PIB in the initial formulation led to a less marked gel effect, explained by the smaller relative variation of free volume with conversion. The dimensionless free volume of PIB obtained from the kinetic model was found to increase with the volume concentration of chain ends, as expected. Under conditions where phase separation took place at very low conversions, the overall polymerization rate exhibited the presence of two maxima (gel effects), representing the polymerization in two different phases. The first maximum was associated with the polymerization taking place in the phase lean in PIB, and the second maximum was associated with the polymerization of the monomer that was initially fractionated with PIB.